Agricultural and forestry use of biochar: state of the art and future research (Research, Society and Development, 2022)
Objective: Biochar is one of the products generated from biomass pyrolysis. Among the various possible applications, one that has been studied over the last few years is the employment of this material as a soil conditioner, aiming to improve properties in agricultural and forestry plantations. Methodology: Thus, this work aims to verify the state of the art of research related to biochar and its application, identifying the main interactions that occur between biochar and the soil, as well as with the elements that compose it. Results and discussion: After reviewing the literature and discussing the main aspects of the use of biochar, it was identified that the two topics that deserve greater attention due to the lack of sufficient work to improve the discussions are related to agricultural machines and implements used for the application of biochar in the soil and the analysis of the economic viability of using this product in plantations. Conclusion: With more work on these two topics, it will be possible to advance and improve the practical aspects of the application of biochar, disseminating this technique that can significantly contribute to the advancement of forestry in Brazil and worldwide.